Affirmative action policies and the evolution of post-apartheid South Africa's racial wage gap - Rulof Burger; Rachel Jafta; Dieter von Fintel (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
Racial wage inequality and discrimination have pervaded South African society for centuries. Apartheid legislation cemented these disparities by institutionalizing white job reservation and many other unfair practices. While racial wage gaps started to decline towards the end of apartheid, they increased (against all expectations) in the immediate post-transition period. Affirmative action legislation was enacted with a lag, first targeting employment equity and skills development in 1998 and then more extensive 'black economic empowerment' in 2003. However, the rise in the racial wage gap only started to reverse in 2005. Existing studies therefore report limited effects of affirmative action policies, with highly skilled occupations still dominated by white men, and racial wage gaps remaining higher than in 1997. This paper develops an updated decomposition methodology that tracks changes in the discrimination component of the wage gap over time. It accounts for biases attributable to changing generational composition of labour market entrants and retirees: this variation is typically incorrectly measured as time evolution, and by implication attributes demographic movements to the effect of policy changes. New evidence shows that 2003 was a turning point, when black-white discrimination started to decline continuously thereafter. The continuing trend suggests that this is a permanent legislative effect rather than a business cycle dividend. However, generational changes (separate from policy effects) have not yet reached a turning point. Results also indicate that the legislation has alleviated previous barriers - by which black wages did not benefit from economic growth before affirmative action legislation was implemented. Notably, the time decline in discrimination can be attributed to the large and growing returns to tertiary education, especially for black men after successive waves of reforms were enacted.
Keywords: J31; J71; 330; affirmative action; discrimination; decomposition techniques; South Africa